2022
DOI: 10.1002/jmv.28234
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome analysis revealing microbial interactions and secondary bacterial infections in COVID‐19 patients comorbidly affected by Type 2 diabetes

Abstract: The mortality of coronavirus disease 2019 (COVID‐19) disease is very high among the elderly or individuals having comorbidities such as obesity, cardiovascular diseases, lung infections, hypertension, and/or diabetes. Our study characterizes the metagenomic features in severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2)‐infected patients with or without type 2 diabetes, to identify the microbial interactions associated with its fatal consequences.This study compared the baseline nasopharyngeal microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…Loss of these commensal bacteria (e.g., Prevotella) from gut microbiomes indicates that Prevotella can act as a local probiotic and counteract SARS-CoV-2 to defend it in patients with COVID-19. 6 In a recent study, the genera Rothia and Shigella were found at elevated levels in the gut microbiomes of SARS-CoV-2 and H1N1 influenza patients, corroborating with the present study's findings. 46 Loss of pathogenic bacterial genera like Porphyromonas and Haemophilus in the gut microbiomes of the COVID-19 diabetes group raises the possibility that other cohabiting bacterial communities may also have adverse effects, such as the loss and deficiency of vital dietary nutrients like minerals and vitamins.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Loss of these commensal bacteria (e.g., Prevotella) from gut microbiomes indicates that Prevotella can act as a local probiotic and counteract SARS-CoV-2 to defend it in patients with COVID-19. 6 In a recent study, the genera Rothia and Shigella were found at elevated levels in the gut microbiomes of SARS-CoV-2 and H1N1 influenza patients, corroborating with the present study's findings. 46 Loss of pathogenic bacterial genera like Porphyromonas and Haemophilus in the gut microbiomes of the COVID-19 diabetes group raises the possibility that other cohabiting bacterial communities may also have adverse effects, such as the loss and deficiency of vital dietary nutrients like minerals and vitamins.…”
Section: Discussionsupporting
confidence: 92%
“…The bacterial genus Prevotella remained considerably lower in abundance in the gut microbiomes of CD compared to HC, possibly suggesting a decrease in commensal bacteria and counteraction against SARS‐CoV‐2 infections. Loss of these commensal bacteria (e.g., Prevotella ) from gut microbiomes indicates that Prevotella can act as a local probiotic and counteract SARS‐CoV‐2 to defend it in patients with COVID‐19 6 . In a recent study, the genera Rothia and Shigella were found at elevated levels in the gut microbiomes of SARS‐CoV‐2 and H1N1 influenza patients, corroborating with the present study's findings 46 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is due to the ability of the gut microbiota to modulate their composition leading to preventive and therapeutic benefits, including the regulation of immune responses [ 217 , 218 , 219 ]. Furthermore, a recent study reported that the dysbiosis of the respiratory microbiome might be linked to the severe effects of COVID-19 diabetic patients [ 220 ].…”
Section: The Microbial Community Characterizationmentioning
confidence: 99%
“…SARS-CoV-2 Variant-wise detection result and percentages. services provided for routine COVID-19 surveillance at the Genome Center, Jashore University of Science and Technology (JUST) authorized by the Directorate General of Health Services (DGHS), Bangladesh26 .…”
mentioning
confidence: 99%